Mail Management System in the Digitalization of Village Administration: A Case Study of Batuyang Village Office, East Lombok - Marlina, Siti; Radhitya, Made Leo (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
One issue with correspondence at the Batuyang Village Office is that letters still kept in the agenda book can lead to file loss if not properly filed. It takes a long time to make letter dispositions since they have to wait for the village chief. So that creating, searching for, and disposing of letters does not take too much time, a web-based program for managing correspondence can offer better and faster filing services. To address these issues, the village office implemented a web-based correspondence administration information system. The system provides officers with up-to-date data and information, facilitating the creation of both outbound and incoming letters.Admin, village head, incoming, outgoing, and letter disposition data are all part of this correspondence information system's data management capabilities. Moreover, it will be able to print disposition successor sheets, generate reports in the form of incoming and departing letters, and more based on the data. In addition, a blackbox testing scenario was used to test the system, and the results showed that all of the available menus functioned properly.